THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND ACADEMIC ACHIEVEMENT OF FIFTH GRADE STUDENTS OF TEGALREJO 1 STATE ELEMENTARY SCHOOL - Desetria Cici; Karunia Estri, Arimbi; Indri Kurniasari, Cecilia (Journal of Nursing Culture and Technology, 2024)
Background: Nutrition is essential for school children's growth, development, energy, cognitive function, and immune system. High-quality nutrition optimizes brain growth and development. Objective: This study aims to determine the relationship between nutritional status and academic achievement among fifth-grade students at SD Negeri Tegalrejo 1, Yogyakarta. Method: This quantitative, correlational study was conducted from March to July 2023 at Jalan Bener No. 40, Tegalrejo, Yogyakarta. Nutritional status and academic performance were assessed using anthropometric measurements (BMI-for-age Z-scores) and final report card grades. The study included 56 students, with 53 ultimately participating due to exclusion criteria (absence during data collection). Data were analyzed using univariate and bivariate analysis with Spearman's correlation test. Result: The results showed no significant relationship between nutritional status and academic achievement (P-value = 0.642, P > 0.05). Conclusions: Factors such as dietary habits, physical activity, motivation, talent, interest, and learning willingness, along with external factors like school environment, family, and socio-economic status, may contribute more significantly. Schools should monitor students' nutritional status through regular height and weight measurements and collaborate with local health facilities. This study focused solely on cognitive aspects of academic achievement, suggesting future research should include a more comprehensive assessment of student performance.